Dampak Serangan Organisme Pengganggu Tanaman dan Perubahan Iklim terhadap Produksi dan Pendapatan Petani Padi Sawah di Sumatera Utara - Nurhijjah, Nurhijjah; Kuswardhani, Retna Astuti; Kardhinata, E. Harso (Universitas Medan Area, 2019)
This study aims to analyze the effect of planting area, harvest area, pest attack area, the effect of flood area and drought area on lowland rice production in North Sumatra Province. The study was conducted for three months from June to August 2016. The form of this study was a quantitative descriptive study with a documentation analysis method. The study uses 5-year time series data (from 2011 to 2015). The rice production center sample areas were selected purposively as many as three production center districts located on the West coast, namely: Deli Serdang Regency, Simalungun Regency and Langkat Regency and three districts in the East Coast region namely: Mandailing Natal Regency, South Tapanuli Regency and Regency Padang Lawas Utara. Analysis using multiple linear regression models with SPSS version 17. The results of this study indicate the R2 value of 97.6% means the variable planting area, harvest area, pest attack area, flood area and drought area simultaneously have a very significant effect on paddy production in research area. Variable planting area, harvested area, pest attack area, flood area and drought area separately have a significant effect on the production of lowland rice in the study area.